The Fostering of Multimodal Text Literacy in Elementary School Learning - Saputra, Dimas Teguh; Rahmawati, Laili Etika; Markhamah, Markhamah Markhamah (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
Literacy is very important for learners, but national assessment results show that their literacy skills are still low. Therefore, multimodal text literacy has become the focus of the Indonesian government in recent years. The purpose of this study is to describe the planning and implementation of multimodal text literacy acculturation in primary schools. The research method used was descriptive qualitative with a phenomenological approach. Data collection techniques were observation, interview and documentation. The results of this study show that multimodal text literacy acculturation in primary schools is carried out by building a multimodal text-rich school environment which is a variation of the form of literacy activities in primary schools. The conclusion is that multimodal text literacy acculturation can be done with various forms of literacy activities. The results of this study provide strategic recommendations for primary schools in improving literacy skills.